(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article analyzes the theoretical and methodological foundations of digital transformation and its impact on regional economic development. Digital technologies are shown to create new value chains, increase management efficiency, reduce transaction costs, and accelerate innovative growth. Using the case of the Bukhara region, the study examines the expansion of digital services, the implementation of e-governance systems, and the development of digital skills within human capital. Furthermore, it compares the experiences of Singapore, South Korea, and Estonia with Uzbekistan’s national “Digital Uzbekistan – 2030” strategy. The findings demonstrate that digital transformation is shaping a new paradigm of regional development, fostering sustainable growth and innovation-driven competitiveness.